Development and Validation of One-Step Reverse Transcription-Droplet Digital PCR for Plum Pox Virus Detection and Quantification from Plant Purified RNA and Crude Extract - Giorgia Bertinelli; Lorenza Tizzani; Marta Luigi; Simona Monticelli; Vincenza Ilardi (Plants)
Plum pox virus (PPV) is the etiological agent of sharka, the most important viral disease of stone fruit worldwide. In this study, a one-step reverse transcription real-time PCR test (RT-qPCR) was modified and translated as a one-step RT-droplet digital PCR (RT-ddPCR) for sensitive, direct, and accurate detection and quantification of PPV. The modified RT-qPCR and RT-ddPCR PPV detection tests were validated using both plant purified total RNA (TRNA) and crude extract as templates. The proposed tests were sensitive, specific, selective, repeatable, and reproducible in detecting PPV from fresh, lyophilized, and in vitro plant samples. RT-ddPCR was more sensitive than RT-qPCR in detecting PPV using purified TRNA while showing the same sensitivity using crude extract. This work highlights the robustness, time-saving, and cost-effective nature of the proposed one-step RT-ddPCR test, offering a potential reduction in resources for PPV detection and quantification even with raw extracts.